A novel, C2-symmetric, chiral bis-cyclosulfinamide-olefin tridentate ligand in Rh-catalyzed asymmetric 1, 4-additions. Issue 29 (18th July 2018) - Zhang, Li; Tan, Mingchao; Zhou, Lihong; Zeng, Qingle
Graphical abstract: Highlights: A novel chiral bis-cyclosulfinamide-olefin tridentate ligand (DICSO) achieved extremely high enantioselectivities (>99%ee). The DICSO is more superior to its structure-similar bidentate ligands. The DICSO ligand has two rigid (S)-1-oxo-2, 3-dihydro-1, 2-benzisothiazole skeletons and a flexible butenylene chain. HRMS and NMR analyses verify that the DICSO as a tridentate ligand coordinates to rhodium(I) to form a complex. Abstract: A C2 -symmetric, chiral bis-cyclosulfinamide-olefin ligand composed of two 1-oxo-2, 3-dihydro-1, 2-benzisothiazole moieties with rigid skeletons and a conformationally flexible butenylene chain is disclosed for the first time. HRMS and 1 H NMR analyses verify that the in situ-generated complex of the ligand and [Rh(C2 H4 )2 Cl]2 possesses a rhodium (I) center coordinated to the tridentate ligand via two sulfinyl moieties and a CdbndC bond. The chiral ligand provided extremely high enantioselectivity (up to >99%ee) in the Rh-catalyzed asymmetric 1, 4-additions of arylboronic acids to cyclohexenone and cyclopentenone. The tridentate ligand gave much higher enantioselectivity than the analogous chiral bidentate ligands.